Synthesis of dendronized polymers by ring opening metathesis polymerization techniques and investigation of biological activities - İslam, Muhammad Nazrul (My University, 2020)
In this thesis, exo-7-oxabicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride was successfully synthesized from furan and maleic anhydride by Diels-Alder reaction. Diels-Alder adduct was conjugated with hydrazine hydrate, ethylenediamine, BOCprotected ethylenediamine, 1,4-diaminobutane and 1,6-diaminohexane linker to get amine surfaced core. Percentage of yield of the product was found higher with the increase of chain length of linker. Percentage of yield for ethylenediamine, 1,4- diaminobutane and 1,6-diaminohexane linker core was 10%, 40%, and 52% respectively. When ethylenediamine was incorporated directly to oxanorbornene, a mixture of exo-endo products was observed which was not easily separable. Pure exo-isomer was required to polymerize the monomer later on. One NH2 of ethylenediamine was protected by di-tert-butyl-dicarbonate (BOC) to get EDABOC.EDA-BOC was incorporated to exo-7-oxabicyclo[2.2.1]hept-5-ene-2,3- dicarboxylic anhydride to get pure exo isomer. BOC was deprotected by trifluoroacetic acid (TFA) to get NH2 surface. Oxanorbornene cored amine surfaced compounds are extended as half generation dendritic compound by treating with methyl acrylate by Michael addition reaction. This process is laborious, multistep and percentage of product quite low. Same compound was synthesized by convergent strategy through 0.5 generation dendron from ethanolamine which was incorporated with furan-maleimide through Mitsunobu reaction. Homopolymer of two carbon liker 0.5 generation dendritic monomer has been synthesized by Grubbs 3rd and 2nd generation catalyst. Similarly, 0.5, 1.5 and 2.5 generation dendritic monomers were synthesized from six carbon linker core through divergent strategy by methyl acrylate and ethylenediamine. Homopolymers from all monomers were synthesized by Grubbs 3rd and 2nd generation catalyst. Targeted molecular weight of homopolymers was 20 kg/mol which was further investigated by GPC and 1H NMR end group analysis. CuPAMAM-ROMP nanoparticles were prepared and catalytical activities of this nanoparticle for conversion 4-nitrophenol to 4-aminophenol were investigated by UV-vis absorption. Again, exo-7-oxabicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, reacts with pyridine-3-ylmethanamine to get pyridine containing monomer which was further converted to pyridinium salt by 1-bromohexane. Finally random and block copolymer of two and six carbon linker 0.5 generation dendritic monomer with pyridinium based quarternary ammonium monomer were synthesized through ROMP by Grubbs third generation catalyst. Targeted molecular weight of copolymers was 10 kg/mol, which were further investigated by GPC in DMSO solvent and 1H NMR end group analysis. After then ester terminated polymers surface were treated by EDA-BOC to get BOC surfaced copolymers. These polymers were modified to be water soluble cationic polymer by TFA to get antibacterial polymers. Antibacterial activities and hemolytic tests of synthesized copolymers have done by serial dilution method. Six carbon linker copolymers were observed high antibacterial activity against Gram-positive bacteria (S. aureus), whereas they were inactive against Gram-negative bacteria (E. coli). Moreover, though molecular weight and monomers feed ratio of monomers kept same, block copolymer shows MIC 32μg/mL but random copolymer shows MIC 64 μg/mL. Hemolytic data shows all the copolymers, except two exemption, are non-toxic ( >1000 μg/mL) against human blood cell. S. aureus incubated with active and inactive polymer and Zeta potential were measured to see relationship between the MIC and membrane surface charge density. Zeta potential of copolymers was found +5.7 mV to +16.3 mV but S. aureus incubated active polymer’s zeta potential found -3.5 mV. Scanning Electron Microscope (SEM) image confirms damage of the bacterial cell wall after implementation of our antimicrobial polymer.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: ROMP; Dendron; Ring opening metathesis polymerization; Antibacterial polymers